Cost Decision Making Using Activity-Based Costing Approach in Digital Information Systems - Harahap, Imam Zarkasih; Irawan, Muhammad Dedi; Valerry, Adele; Zarkasih Harahap, Imam (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2025)
This study aims to develop and apply the Activity-Based Costing (ABC) method in determining overhead costs in the rice processing industry at MGS Tanjung Selamat Rice Mill. Conventional methods often cause distortions in the allocation of overhead costs, which have an impact on the inaccuracy in the calculation of the cost of goods manufactured (COGS). To overcome this problem, this research uses a Research and Development (R&D) approach with a system development model based on the Waterfall method. Data were collected through observations, interviews, and documentation studies, which were then analyzed to identify the main production activities and the most influential cost drivers. The results showed that the ABC method was able to improve the accuracy of overhead cost calculation, optimize cost allocation to each production activity, and support more strategic business decision-making. In addition, this research produced a software-based system to facilitate the implementation of the ABC method in the company. With the implementation of ABC, MGS Tanjung Selamat Rice Mill can set a more competitive selling price and identify less efficient activities to be improved.